2024
DOI: 10.1002/jmd2.12410
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological stability in classical galactosemia: A pilot study in 10 adult patients

Merel E. Hermans,
Gert J. Geurtsen,
Carla E. M. Hollak
et al.

Abstract: Classical galactosemia (CG) is an autosomal recessive disorder of galactose metabolism. Despite early initiation of a galactose‐restricted diet, patients develop long‐term complications including cognitive impairment. There is an ongoing debate whether the cognitive impairment in CG is stable throughout life or progresses with age. Earlier cross‐sectional and longitudinal studies regarding intelligence suggest stability, but longitudinal neuropsychological studies focusing on specific cognitive functions are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A recent study in a robust dataset of CG patients (mean age of 18 years) concluded that speech/voice/language, cognitive, motor, and psychosocial outcomes are not progressive in most patients, but also here the time between testing was limited ( Smith et al, 2023 ). A pilot study with 10 adult patients (mean age 33 years) and a mean time interval of 3 years and 9 months reported cognitive stability ( Hermans et al, 2024 ).…”
Section: Brain Function Through Adulthoodmentioning
confidence: 99%
“…A recent study in a robust dataset of CG patients (mean age of 18 years) concluded that speech/voice/language, cognitive, motor, and psychosocial outcomes are not progressive in most patients, but also here the time between testing was limited ( Smith et al, 2023 ). A pilot study with 10 adult patients (mean age 33 years) and a mean time interval of 3 years and 9 months reported cognitive stability ( Hermans et al, 2024 ).…”
Section: Brain Function Through Adulthoodmentioning
confidence: 99%